Convergence analysis of a perturbed iterative scheme (PIS) for solution of nonlinear systems. (1981) - Dey, S. K.
Abstract : In the references [1, 2, 3] a perturbed iterative scheme (PIS) has been studied both theoretically and computationally to solve nonlinear equations. In this article a more general analysis of its convergence properties has been done